Eksistensi Ombudsman RI Perwakilan Sumatera Barat dalam Pencegahan Maladministrasi Sebagai Bentuk Pengawasan Terhadap Penyelenggaraan Pelayanan Publik - Hergiansyah Hergiansyah; Syafirman Syafirman; Rizki Syafril (Universitas Palangka Raya, 2024)
To carry out public services and all activities carried out by state administrators, a state institution is needed that functions and is tasked with supervising the running of public services and state administrators. All forms of complaints and aspirations complained by citizens were all accommodated so that a state ombudsman institution was formed. The Ombudsman of the Republic of Indonesia itself is a state institution that oversees the implementation of public services and maladministration is included in its authority. Supervision is carried out including those carried out by BUMN, BUMD, State-Owned Legal Entities, and private bodies or individuals whose task is to carry out certain public services, all or part of whose funds come from the APBN/APBD. The data that has been obtained comes from a literature review which is then analyzed using content analysis techniques. Human behavior can be studied indirectly by researchers by observing interactions through various media sourced from online news, newspapers, textbooks, journals, and various other types of communication that can be analyzed.